Pandangan MUI Kota Medan terhadap Penyimpangan Aqidah Islam Dalam Masyarakat di Indonesia - Rahmi, Siti; Mutiah, Rizkiyani; Hamdani Hsb, Miswar; Wulandari, Winda; Ulul Bhari, Muhammad; Iqbal, Mhd; Khartarya, Alvita (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
Understanding, examples, and phenomenological methods are used in this study to apply the phenomenology method. which a group of people in his life consciously and individually experience. The research for this thesis aims to discover Medina's perspective on the social deviations of Islamic aqeedah. Medan MUI is of the opinion that the deviance from Islamic aqeedah is a matter that is connected to the principles underlying Islamic teachings. As a result, unity is required in aqeedah, the fundamental understanding of the faith. The touching goes against and contradicts the fundamentals of Islamic teachings that have been qath'i, such as those related to faith and others. Keywords: Deviations, Islamic Aqeedah, MUI, Medan City.